1999
DOI: 10.1074/jbc.274.51.36729
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Nitric-oxide Synthase in Plant Peroxisomes

Abstract: The presence of nitric-oxide synthase (NOS) in peroxisomes from leaves of pea plants (Pisum sativum L.) was studied. Plant organelles were purified by differential and sucrose density gradient centrifugation. In purified intact peroxisomes a Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
201
1
11

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(220 citation statements)
references
References 42 publications
7
201
1
11
Order By: Relevance
“…5 Subcellular compartmentalization of iNOS within peroxisomes has been shown to occur in plants, although it was not associated with any physiologic consequence distinct from that of cytosolic iNOS. 37 Here we show that peroxisomal localization of iNOS can be associated with reduced expression of catalase. Previous studies have indicated that NO can inactivate catalase reversibly in hepatocytes 38 and reduce catalase expression in C6 glioma cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…5 Subcellular compartmentalization of iNOS within peroxisomes has been shown to occur in plants, although it was not associated with any physiologic consequence distinct from that of cytosolic iNOS. 37 Here we show that peroxisomal localization of iNOS can be associated with reduced expression of catalase. Previous studies have indicated that NO can inactivate catalase reversibly in hepatocytes 38 and reduce catalase expression in C6 glioma cells.…”
Section: Discussionmentioning
confidence: 94%
“…Although iNOS has been shown to localize to plant peroxisomes, 37 this is the first report of iNOS expression within animal cell peroxisomes in response to septic stress and, more specifically, in an organ that is one of the body's initial defenses against infections. 44 Kupffer cells, the resident macrophages of the liver, also express iNOS (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Initial evidence was based on the production of NO and L-citrulline from L-Arg by plant extracts and/or its inhibition by specific inhibitors, typically inactive substrate analogs (Cueto et al, 1996;Ninnemann and Maier, 1996;Delledonne et al, 1998;Durner et al, 1998). In a different approach, the use of antibodies against mammalian NOS enzymes detected immunoreactive proteins in different plant cell compartments (Barroso et al, 1999;Ribeiro et al, 1999). However, subsequent identification of the cross-reacting polypeptides using matrix-assisted laser desorption/ionization-time of flight mass spectrometry demonstrated that the mammalian antibodies recognized plant proteins unrelated to NOS (Butt et al, 2003), making this strategy inappropriate to infer the presence of plant NOS.…”
Section: First Leads In the Hunt For Plant Nos Enzymesmentioning
confidence: 99%
“…NO stimulates seed germination in different species, and a decrease in NO levels has been associated with fruit maturation and senescence of flowers (Beligni and Lamattina, 2001). NO production has been observed in response to several biotic and abiotic stimuli, such as pathogen infection, bacterial elicitors, high temperature, osmotic stress, and UV-B light (Durner et al, 1998;Barroso et al, 1999;Krause and Durner, 2004;Zeidler et al, 2004;Shapiro, 2005;Corpas et al, 2008;Kolbert et al, 2008;Zhao et al, 2009).…”
mentioning
confidence: 99%